A Tale of Two Cities - Charles Dickens; Phiz; James Weber Linn (New York Charles Scribner's Sons, 1911)
Standard English Classics
With 16 illustrations by Phiz
The Centennial Edition of The Works of Charles Dickens in 36 Volumes .
Keywords: Literature (3GdCOHs; General